Preparation and Characterization of Titanium Dioxide (TiO ) Thin Films Prepared By Spin Coating Method 2 - Ahmed J. hassan (University of Thi-Qar Journal of Science, 2019)
Transparent semiconducting thin films of titanium dioxide (TiO2-) were deposited on glass substrates by spincoatingtechnique and with thickness was in order of 150 ± 5 nm . The XRD analysis reveals that the films arepolycrystalline with an anatase crystal structure and a preferred grain orientation in the (101) direction. The opticalproperties of the films were characterized by UV–visible spectrophotometry, which shows that the films are highlytransparent in the visible and near infrared , with an average value above (99 %), with energy gape (3.79 e.v ). Thedependence of the refractive index (n), extinction coefficient (k), and absorption coefficient (α) of the films on thewavelength was investigated.